Análisis de comparación en rentabilidad de Almacén Skegui durante el periodo 2019-2020 - Figueroa Moreno, Karen Danixa (2021)
This work aims to analyze and compare the profitability of the Skegui warehouse during the 2019-2020 period, this organization was taken into account because it has been in the commercial sector for years, therefore it was verified in terms of profitability, according to this commercial area, the Organizations that operate in these sectors have a high capital ratio and higher margins, but lower turnover, than those that operate in competitive markets, and otherwise these are defined by their economic profitability with high turnover that compensates for the lower margins. Within the commercial sector, organizations that achieve higher margins tend to have higher financial profitability, this is obtained in the same way as economic profitability, that is, enhancing the margin once the usual rotation of the sector is achieved, since the degree of Investment leverage does not appear to have any impact on the wealth creation capacity of small businesses, in this case the Skegui Warehouse.